Prediction of reheat cracking behavior in a service exposed 316H steam header - Zhou, Haoliang; Mehmanparast, Ali; Nikbin, Kamran (World Scientific Publishing, 2020)
Reheat cracking in an ex-service Type 316H stainless steel steam header component has been investigated in this study. The examined steam header was in service for 87,790" role="presentation" style="display: inline; line-height: normal; word-spacing: normal; overflow-wrap: normal; white-space: nowrap; float: none; direction: ltr; max-width: none; max-height: none; min-width: 0px; min-height: 0px; border-width: 0px; border-style: initial; position: relative;">h and the cracks in this component were found in the vicinity of the weld toe. The root cause of this type of failure was due to the welding residual stresses. The welding-induced residual stresses had been present in the header at the early stage of the operation and were released during service. In this paper, a novel technique has been proposed to simulate the residual stress distribution normal to the crack direction by applying remote fixed displacement boundary conditions in an axisymmetric model. This approach can simulate the presence of residual stresses in actual components without the need to develop full weld simulation to quantify them. The predicted residual stress levels and distributions normal to the crack direction have been found in good agreement with the measured residual stresses available in the literature for a similar header. The creep crack growth (CCG) rates have been characterized using the fracture mechanics C∗" role="presentation" style="display: inline; line-height: normal; word-spacing: normal; overflow-wrap: normal; white-space: nowrap; float: none; direction: ltr; max-width: none; max-height: none; min-width: 0px; min-height: 0px; border-width: 0px; border-style: initial; position: relative;">C∗C∗ parameter and estimated using predictive models.
Keywords: C∗ correlation; (CCG)316H; creep crack growth; residual stresses; Reheat cracking